Resident Experiences with and Post-Training Plans for Cystoscopy at the Time of Hysterectomy. (November 2015) - Vaynberg, Dina; White, Chase; Jaspan, David; Lentz, Gretchen; Goldberg, Jay
Aims: To determine OB/GYN residents' experience with and opinions toward cystoscopy at the time of hysterectomy.Study design: An internet survey of OB/GYN residents assessed utilization of cystoscopy at the time of hysterectomy, familiarity with literature regarding universal versus selective cystoscopy, and plans post residency.Results: Cystoscopy was performed universally in the minority of cases of vaginal hysterectomy (12%), laparoscopically assisted vaginal hysterectomy (14%), supracervical hysterectomy (0%), total abdominal hysterectomy (2%), laparoscopic supracervical hysterectomy (9%), total laparoscopic hysterectomy (27%), and hysterectomy with adnexa removal (5%). Residents planned universal cystoscopy post-training more frequently for all hysterectomy types.Conclusion: Cystoscopy at the time of hysterectomy was performed universally in the minority for all hysterectomy categories. For all hysterectomy types, residents planned post-graduation to utilize universal cystoscopy at the time of hysterectomy more often than occurred in training.